Why Mental Illness Diagnoses Are Wrong: A Pilot Study on the Perspectives of the Public - Chao, Yi-Sheng; Wu, Chao-Jung; Lai, Yi-Chun; Hsu, Hui-Ting; Cheng, Yen-Po; Wu, Hsing-Chien; Huang, Shih-Yu; Chen, Wei-Chih (Frontiers in Psychiatry, 2022)
Background Mental illness diagnostic criteria are made based on assumptions. This pilot study aims to assess the public’s perspectives on mental illness diagnoses and these assumptions. Methods An anonymous survey with 30 questions was made available online in 2021. Participants were recruited via social media, and no personal information was collected. Ten questions focused on participants’ perceptions regarding mental illness diagnoses, and 20 questions related to the assumptions of mental illness diagnoses. The agreement between participants’ perspectives and the mental illness symptoms assumed by professionals was assessed. Results Among 14 survey participants, 4 correctly answered the relationships of 6 symptom pairs (28.57%). Two participants could not correctly conduct the calculations involved in mood disorder diagnoses (14.29%). Eleven (78.57%) correctly indicated that 2 or more sets of criteria were available for single diagnoses of mental illnesses. Only 1 (7.14%) correctly answered that the associations between symptoms and diagnoses were supported by including symptoms in the diagnostic criteria of the diagnoses. Nine (64.29%) correctly answered that the diagnosis variances were not fully explained by their symptoms. The confidence of participants in the major depressive disorder diagnosis and the willingness to take medications for this diagnosis were the same (mean = 5.50, standard deviation [SD] = 2.31). However, the confidence of participants in the symptom-based diagnosis of non-solid brain tumor was significantly lower (mean = 1.62, SD = 2.33, p < 0.001). Conclusion Our study found that mental illness diagnoses are wrong from the perspectives of the public because our participants did not agree with all the assumptions professionals make about mental illness diagnoses. Only a minority of our participants obtained correct answers to the calculations involved in mental illness diagnoses. In the literature, neither patients nor the public have been engaged in formulating the diagnostic criteria of mental illnesses.